The effect of broccoli stem extract cream (Brassica oleracea L.) on macular scars post-acne - Syahputri, Fitriend; Putra, Imam Budi; Jusuf, Nelva Karmila (Frontiers in Medicine, 2025)
IntroductionPost-acne macular scars often cause skin discoloration, affecting appearance and self-confidence. To address this issue, various topical therapies have been developed. Broccoli (Brassica oleracea L.) is widely cultivated in North Sumatra. Broccoli stem, typically discarded as a byproduct, represents a sustainable resource that can be repurposed for skincare applications. Broccoli stem extract contains bioactive constituents, including sulforaphane and flavonoids, which exhibit antioxidant and anti-inflammatory activities. These properties suggest its potential role in improving post-acne macular scars.ObjectivesTo analyse the effects of 6% broccoli stem extract cream (Brassica oleracea L.) on post-acne macular scars.MethodsThis quasi-experimental pretest-posttest study included 30 male and female subjects aged ≥18 years with post-acne macular scars, selected according to inclusion and exclusion criteria. Baseline data, melanin index, and erythema index were assessed before and after applying 6% broccoli stem extract cream for 8 weeks. The Wilcoxon signed-rank test was used for data analysis, with statistical significance set at p < 0.05.ResultsMost subjects were women in the late adolescent age group (18–25 years). Statistically significant reductions (p < 0.001) were observed in both the melanin index and erythema index after 8 weeks. Clinical improvement was evident, and no adverse effects were reported, highlighting the cream’s safety for sensitive post-inflammatory skin. All subjects (100%) reported satisfaction with the cream.ConclusionThe use of 6% broccoli stem extract cream effectively improved pigmentation and reduced melanin and erythema indices in post-acne macular scars. Its good tolerability and high patient satisfaction support its potential as a natural, safe alternative to conventional topical therapies.